2002
DOI: 10.1007/s00424-002-0872-3
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin and meta-vinculin in fast and slow rat skeletal muscle before and after hindlimb suspension

Abstract: The role of vinculin and meta-vinculin, the major components of costameres, was explored by analysing quantitatively the expression of these proteins in a slow-twitch (soleus) and in a fast-twitch (extensor digitorum longus, EDL) skeletal muscle under control conditions and after a reduced functional demand. Meta-vinculin, previously observed essentially in smooth and cardiac muscle, was also present in EDL, in the same amount as vinculin. The soleus contained exclusively vinculin, the amount of which exceeded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…In addition, ultrastructural studies have clearly shown that membrane folding and the length of the membrane interface between muscle fiber and tendon are largely increased after hindlimb suspension (91) and spaceflight (63), which might confirm the increase in collagen content in disuse situations. Our previous work conducted with muscle unloading (in both humans and animals) also reported structural changes affecting the expression of several cytoskeletal and associated proteins (22)(23)(24). Together, these results show that collagen and ECM components play a major role in remodeling of skeletal muscle during disuse-induced atrophy.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, ultrastructural studies have clearly shown that membrane folding and the length of the membrane interface between muscle fiber and tendon are largely increased after hindlimb suspension (91) and spaceflight (63), which might confirm the increase in collagen content in disuse situations. Our previous work conducted with muscle unloading (in both humans and animals) also reported structural changes affecting the expression of several cytoskeletal and associated proteins (22)(23)(24). Together, these results show that collagen and ECM components play a major role in remodeling of skeletal muscle during disuse-induced atrophy.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, it has been shown recently that a change in mechanical load in rat skeletal muscle results in increased metavinculin expression (50). Moreover, it is known that smooth muscle cells in culture down-regulate the expression of metavinculin very rapidly (51), possibly because of the lack of external stimuli, such as mechanical stretching.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of metavinculin expressed in human cardiac tissue appears greater than that in mouse (84). Metavinculin levels can be increased by mechanical loading, as has been determined with rat skeletal muscle (15). Subcellularly, metavinculin and vinculin colocalize.…”
mentioning
confidence: 87%